Examining the impact of classroom teaching reforms and virtual learning environments - Shiyong, Song (American Journal of Creative Education, 2023)
Break through the identity characteristics of the virtual teaching and research office at present and provide ideas for how the virtual teaching and research office can become the platform for theoretical and practical teaching. Without considering insufficient funds, this paper analyzes and discusses the ideal construction of virtual teaching and research offices from three aspects: team building, platform construction, sustainable development construction, etc. Theoretical and practical instructors should enter the classroom in a variety of forms together, directing students as they engage in professional learning without relying on rigidly constructed platform resources. As long as the team members have the same ideas, can cooperate sustainably, and truly consider students, the construction goal of the virtual teaching and research room can be achieved. The Virtual Teaching and Research Room is a cross-professional and cross-regional collaborative teaching model that has emerged in recent years with the continuous growth of the demand for teaching specialization and practice and the continuous improvement of Internet technology. Although the virtual teaching and research office theoretically has an unmatched advantage over traditional physical teaching and research rooms, However, in practice, it is too difficult to implement it universally due to the limited funds of colleges and universities. This article provides a reference path for implementing and applying virtual teaching and research rooms in teaching process.